INHIBITION OF CYSTEINE PROTEASES AND ANTIBACTERIAL ACTIVITY OF RHIZOSPHERE-MICROBIAL ISOLATES OF JUSTICIA WYNAADENSIS - RAJESHWARI.K; MANJULA.I.K (International Journal of Pharma and Bio Sciences, 2015)
Proteases are proteolytic enzymes secreted by most pathogenic microorganisms during their mode of entry into the host system. Many pathogenic bacteria such as Staphylococcus aureus produce proteases during infection and due to their emergence as antibiotic resistance, pose problems and threat for efficient control of bacterial diseases. To control such pathogenicity, mediated by the secretion of proteases, protease inhibitor of microbial origin from medicinal plant, Justicia wynaadensis plant-rhizosphere microorganisms were screened, to check their possible role in inhibiting the proteolytic activity and antibacterial effect against the pathogenic organisms such as Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas sp, and Escherichia coli. Broth dilution assays were performed to check antibacterial activity.